Choosing and Using Information in Evaluation Decisions - Katherine B. Coffman; Scott Kostyshak; Perihan O. Saygin (Center for Economic Studies and ifo Institute (CESifo), 2024)
Most studies of gender discrimination consider how male versus female candidates are assessed given otherwise identical information about them. But, in many settings of interest, evaluators have a choice about how much information to acquire about a candidate before making a final assessment. We use a large controlled experiment to explore how this type of endogenous information acquisition amplifies discriminatory outcomes in a simulated hiring environment. Across evaluators, we vary the composition of candidate pools, exploring not only environments where men outperform women on average but also environments with no gender difference or with a female advantage. Perhaps surprisingly, we observe no gender discrimination overall: conditional on their likelihood of being qualified, male and female candidates receive indistinguishable evaluations. But, we observe important differences across candidate pools. Candidates belonging to an advantaged group—the gender with the performance advantage in the pool—receive significantly better evaluations than equally qualified candidates in pools with no gender gap in performance. Similarly, candidates belonging to a disadvantaged group—the gender with a performance disadvantage in the pool—receive significantly worse evaluations relative to equally qualified candidates in pools with no gender gap in performance. This "relative advantage" bias appears in initial assessments, influences how evaluators update their beliefs about a candidate after acquiring more information, and persists in final evaluations. This bias has a significantly larger impact on evaluations when evaluators endogenously acquire information compared to treatments where we exogenously provide it, in part because we observe significant under-acquisition of information. We show that this bias leads to two important types of mistakes: evaluators miss out on talented candidates from disadvantaged groups and over-select less talented candidates from advantaged groups.
Keywords: J16; J71; 330; discrimination; information acquisition; beliefs; belief updating; stereotypes